Peran Financial Technology Dalam Meningkatkan Kualitas Pelayanan Pada Bank Muamalat Balaikota Medan - Harahap, Lailatul Husnah (Universitas Labuhanbatu, 2023)
This study aims to find out the role of fintech in improving service quality and what are the obstacles to implementing fintech in improving service quality at Bank Muamalat Balaikota Medan. The research method used in this researchis descriptive qualitative with data collection techniques carried out by observation, interviews and document studies. Data analysis techniques are carried out by fulfilling four stages, namely data collection, data reduction, data display and drawing conclusions. Based on the results of research and data analysis, it was concluded that first, the role of fintech is very important to improve service quality. Second, the obstacles faced in its implementation are infrastructure and human resources (HR).